Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3382/ps.2014-03981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of commercial in ovo injection of 25-hydroxycholecalciferol on bone development and mineralization in male and female broilers , ,

Abstract: Improved bone development and mineralization in broilers have been attributed to the use of 25-hydroxylcholecalceiferol [25(OH)D3] as a dietary supplement. In this study, effects of the in ovo injection of 25(OH)D3 delivered in commercial diluent on 18 d of incubation (doi) on subsequent bone development and mineralization in male and female Ross × Ross 708 broilers were investigated. The variables investigated included bone mineral density and breaking strength, bone ash concentration, and calcium and phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…(2013) reported that broiler hatching eggs that received in ovo injections of 5.4 μg of 25OHD 3 resulted in broilers having higher PYM and lower PYDM values in comparison with those that received treatment levels that ranged between 0.3 and 1.2 μg. In addition, in ovo injection of 0.6 μg of 25OHD 3 has been shown to increase PYM ( Bello et al., 2013 ) and bone quality ( Bello et al., 2014b ) in broilers in comparison with those injected with diluent alone. Similarly, the 2 vitamin D 3 sources used together at higher doses of injection in the present study resulted in a higher PYM and a lower PYDM in broilers in comparison with those in response to 0.60 and 1.20 μg levels.…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) reported that broiler hatching eggs that received in ovo injections of 5.4 μg of 25OHD 3 resulted in broilers having higher PYM and lower PYDM values in comparison with those that received treatment levels that ranged between 0.3 and 1.2 μg. In addition, in ovo injection of 0.6 μg of 25OHD 3 has been shown to increase PYM ( Bello et al., 2013 ) and bone quality ( Bello et al., 2014b ) in broilers in comparison with those injected with diluent alone. Similarly, the 2 vitamin D 3 sources used together at higher doses of injection in the present study resulted in a higher PYM and a lower PYDM in broilers in comparison with those in response to 0.60 and 1.20 μg levels.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Effects of the in ovo injection of 25OHD 3 alone at various dosage levels on the hatchability, hatching chick quality, and the posthatch production and performance of broilers have been investigated ( Gonzales et al., 2013 , Bello et al., 2013 , Bello et al., 2014a , Bello et al., 2014b , Bello et al., 2014c , Bello et al., 2015 , Mansour et al., 2017 ). However, those effects on the broiler embryo have not been investigated when D 3 is administrated at 18 doi by amniotic in ovo injection alone or in combination with 25OHD 3 .…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Zinc is less efficiently absorbed from the yolk in the final stages of incubation compared with in other minerals . Nutritional supplementation in ovo also helps in overall proper bone development . Researchers have studied the in ovo feeding of probiotics and/or nano‐forms of zinc, copper, and selenium over the health of the embryo and the results were very encouraging.…”
Section: Nutrient Utilization By Developing Chick Embryomentioning
confidence: 99%
“…Furthermore, this technique ameliorated the immune response and increased the resistance against diseases, which resulted in low posthatch mortality and morbidity (Ferket, 2011). The micronutrients, vitamins, trace elements, amino acids, vaccines and functional feed additives can be injected to help the high-metabolism and fast-growing of broiler embryos (Bello, Hester, Gerard, Zhai, & Peebles, 2014;Foye, Ferket, & Uni, 2007;Goel, Bhanja, Mehra, Majumdar, & Pande, 2013;Goel, Bhanja, Mehra, Mandal, & Pande, 2016;Hassan, 2018;Lee et al, 2010;Macalintal, 2012;Pender et al, 2017;Sogunle, Elangovan, David, Ghosh, & Awachat, 2018;Zhai, Bennett, Gerard, Pulikanti, & Peebles, 2011).…”
Section: Introductionmentioning
confidence: 99%